Acquisition rate of antibody to hepatitis B surface antigen among medical and dental students in Japan after three-dose hepatitis B vaccination. Issue 1 (3rd January 2019) - Nagashima, Shintaro; Yamamoto, Chikako; Ko, Ko; Chuon, Channarena; Sugiyama, Aya; Ohisa, Masayuki; Akita, Tomoyuki; Katayama, Keiko; Yoshihara, Masaharu; Tanaka, Junko
Abstract: Background: Health care workers (HCWs) are at high risk of contracting blood-borne infections including hepatitis B virus (HBV) infection. In Japan, all HCWs are required to receive HB vaccination before beginning work. This study aimed to investigate the dynamics of the HB surface antibody (anti-HBs) titer after a three-dose HB vaccination in HCWs and to determine effective scheduling of HB vaccination for non-responders. Methods: Subjects included 832 medical and dental students who had received a three-dose HB vaccination (Bimmugen® 0.5 ml/vial). Anti-HBs was measured three times (before the third dose and 1 and 5 months after the third dose) using the CLIA method. The cut-off value of anti-HBs acquisition was 10 mIU/mL. After booster doses (three maximum) were administered to non-responders, the anti-HBs titers were measured again. Results: Out of 832 students, 491 were analyzed, of which 58.9% (289) were male. Anti-HBs-positive rates before the third dose and 1 and 5 months later were 47.9%, 95.9%, and 89.0%, respectively. The relationship between the antibody titer at one month (x) and 5 months (y) was estimated by log10 y = log10 x − 0.134 (P < 0.0001). Twelve non-responders were followed-up, all of which acquired a protective anti-HBs titer after revaccination with a three-dose booster. Conclusion: Anti-HBs titer decreases by an average of 20% within 4 months between the 1st and 5th month after the third dose. Therefore, anti-HBs titer should be measured periodically after completing the three-dose vaccination. Additionally, results suggested that booster doses are effective if administered with the same schedule as primary vaccination.